Érotique du couple lesbien à l'époque moderne : Diane et ses nymphes - Frédérique Villemur (Images Re-Vues)
Upstream the invention of female homosexuality, research focuses on the visibility of a lesbian éros in modern art, around the figure of the couple, in the representations of Ovid's Metamorphoses linked to the stories of Diana and Actaeon and of Diana and Callisto. The critical gaze is less on the metamorphosis itself as mutation of genders, than on edge figures, which bring into play in the visual device couples of nymphs around Diana at the bath. Lesbian erotica associated with gesture of intimacy questions the affects at the origin of the works, a certain desire to see conveyed by the patriarchal imagination, as it questions the place of the contemporary viewer: how to gaze according to its gender and sexuality?